Problematyka zachodniosłowiańskich grodów plemiennych w świetle badań archeologicznych w dorzeczu dolnej Parsęty. - Brzostowicz, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
This article presents tribal gords in the West Slavic Territory. The analysis was performed on the lower Parsęta basin and selected regions in Poland (chiefly Wielkopolska, Małopolska and Mazowsze). Considerable attention was paid to the origin of the gords, their function and role at a time preceding establishment of the early medieval state structures.